Logic and Education - Oscco López, Rómulo (2014)
This article has as claim show the relationship between logic and education, for it seeks to link the verification criteria and comparison with regard to the language used both in the construction of knowledge as well as the management of the knowledge that has to be taught. It is therefore, from our perspective, needed both the content that has been to teach as the teaching that is done on this.